B-vitamin deficiency causes hyperhomocysteinemia and vascular cognitive impairment in mice - Troen, Aron M; Shea-Budgell, Melissa; Shukitt-Hale, Barbara; Smith, Donald E; Selhub, Jacob; Rosenberg, Irwin H (Proceedings of the National Academy of Sciences - PNAS, 2008)
In older adults, mildly elevated plasma total homocysteine (hyperhomocysteinemia) is associated with increased risk of cognitive impairment, cerebrovascular disease, and Alzheimer's disease, but it is uncertain whether this is due to underlying metabolic, neurotoxic, or vascular processes. We report here that feeding male C57BL6/J mice a B-vitamin-deficient diet for 10 weeks induced hyperhomocysteinemia, significantly impaired spatial learning and memory, and caused a significant rarefaction of hippocampal microvasculature without concomitant gliosis and neurodegeneration. Total hippocampal capillary length was inversely correlated with Morris water maze escape latencies (r = -0.757, P < 0.001), and with plasma total homocysteine (r = -0.631, P = 0.007). Feeding mice a methionine-rich diet produced similar but less pronounced effects. Our findings suggest that cerebral microvascular rarefaction can cause cognitive dysfunction in the absence of or preceding neurodegeneration. Similar microvascular changes may mediate the association of hyperhomocysteinemia with human age-related cognitive decline.